The Effect of Betel Leaf Decoction and Consumption of Boiled Eggs on Perineal Wound Healing in Postpartum Mothers at Cikulur Health Center in 2022 - Ninik Indayani; Novia Juliawati (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
To find out the effect of boiled betel leaf and boiled egg consumption on perineal wound healing in postpartum women at the Cikulur Health Center in 2022. This type of research used a quasy experiment. The reachable population is 30 pregnant women who meet the inclusion criteria in the working area of the Cikulur Public Health Center. The sampling technique uses the total population method. The statistical test used is multiple linear regression. The results showed that the significant value (Sig) of the betel leaf stew variable was 0.003. Because the value of Sig. 0.003 < probability of 0.05, it can be concluded that H1 is accepted and Ho is rejected. This means that there is a significant effect of betel leaf decoction (X1) on perineal wound healing (Y). These results can be concluded that perineal wound healing in post partum mothers can heal completely within 7 days. It is known that the significance value (Sig) of the boiled egg variable is 0.013. Because the value of Sig. 0.013 < probability of 0.05, it can be concluded that H1 is accepted and Ho is rejected. This means that there is a significant effect of boiled eggs (X1) on perineal wound healing (Y). These results can be concluded that perineal wound healing in post partum mothers can heal completely within 7 days. From the results of this study it can be concluded that perineal wound healing in post partum mothers can heal completely within 7 days. With this research, mothers can increase their knowledge about the effectiveness of betel leaf decoction and boiled eggs, and want to carry out the recommendations of health workers.